In order to achieve planning consensus, involvement of stakeholders in coastal zone management, have to be concerned. The participatory prospective analysis (PPA) is a comprehensive and quickly operational framework designed to fulfill the demand for a well-structured effort of anticipation and exploration, that also focuses on interactions and consensus building among stakeholders. PPA was carried out through an expert meeting for coastal zone management planning, as a part of developing syst - A. Aman Damai; Mennofatria Boer; Marimin .; Aria Damar; Ernan Rustiadi (Forum Pasca Sarjana, 2011)
In order to achieve planning consensus, involvement of stakeholders in coastal zone management, have to be concerned.   The participatory prospective analysis (PPA) is a comprehensive and quickly operational framework designed to fulfill the demand for a well-structured effort of anticipation and exploration, that also focuses on interactions and consensus building among stakeholders. PPA was carried out through an expert meeting for coastal zone management planning, as a part of developing system of coastal zone spatial planning, in Lampung Bay. The PPA was aimed to involve stakeholders to generate identification and definition of key variables, definition of the states of variables in the future, building scenarios, and formulation of strategic implications and anticipated actions for coastal zone management. A number of 27 participants from various representative backgrounds, i.e.: local government, fisherman and aqua culturist, local people and entrepreneurs, and local university, was involved in experts meeting. As a result was obtained 6 variables that have the largest influence in coastal zone management of Lampung Bay, they are: quality of human resource, law enforcement, population growth, regional infrastructure, local economic activities, and regional zoning. Consensually, participants was  invented strategic implications and anticipated actions, that have to be accommodated in  coastal zone  management, they are: (1) accomplish requirement of infrastructure and facilities of health and education; (2) develop of micro, small, and medium business (MSMB)  centers  that associated with marine and fisheries; (3) accomplish requirement of housing that comprise proper infrastructure and sanitation facilities; (4) assembly synergy on spatial arrangement among cities  and regencies; (5) assembly spatial arrangement which able to drive development of MSMB in coastal zone; (6) assembly spatial arrangement which able to drive proportional distribution of population in coastal zone, and also proportionally secure the management of conservation and production areas.  Finally, it is concluded that: (1) the PPA could accomplish  direct interactions among  stakeholders intensively and generate consensus opinions; (2) the PPA could be a platform for stakeholders involvement in order to  establish keys variable of planning, define  future states of variables, scenarios building, and strategic implications and anticipated actions for integrated planning of coastal zone of Lampung Bay; (3) stakeholders involvement is the key of  simplification  of policies formulation for  integrated planning of coastal zone of Lampung Bay, in which various of interest could be accommodated.   Key words:  participatory prospective analysis, stakeholders, consensus, coastal zone management, Lampung Bay